OD TOTALITARYZMU DO HUMANITARYZMU. LITERACKIE WIZJE PRAWA RZYMSKIEGO - Kuryłowicz, Marek (Zeszyty Prawnicze, 2016)
FROM TOTALITARIANISM TO HUMANITARIANISM. LITERARY VISIONS OF ROMAN LAW Summary In literary works the Roman law usually performs the part of the symbol of law, either just and human or bad and unfair according to needs. Those visions became one of the paths to create the notion of Roman law and its universal role in European history. The article shows such examples from the Polish literaturę For the 19th century it was characteristic to regard the history of Rome as an opposition of imperial, totalitarian and pagan state and the nascent and finally triumphing Christian Rome. In the 20th century there appears a literary symbol of Roman law as humanitarian law established by the people to fulfill free thought and justice. Such an image was born in certain times as a reaction to fascist and communist experience of totalitarian states, when Roman law – according to literary wording (L. Aragon; M. Jastrun) – for some time „ceased to exist”. Consequently we have to do with a dual literary vision of Roman law. In the totalitarian Roman state in antiquity the law served the authorities and was an instrument to achieve imperial purposes. Two thousands years later, in 20th century, Roman law confronted with totalitarian states becamea symbol of humanitarian and just law. This interesting subject is certainlyworth further investigation.